Tools, Methodologies and Techniques Applied to Sustainable Supply Chains - García-Alcaraz, Jorge Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Supply chains are currently globalized and companies operate internationally owing to the fact that raw materials, production processes, and the consumption of the final products are carried out in different countries. This implies high material and information flow, which incurs high costs associated with the supply chain and logistics, sometimes up to 60% of the total cost of the product. Therefore, companies seek to optimize their resources to reduce these costs and improve sustainability in a globalized market. This book, entitled Tools, Methodologies and Techniques Applied to Sustainable Supply Chains, contains 15 chapters that report case studies applied to industrial and service sectors. The authors come from areas such as Mexico, Colombia, Italy, Sweden, Slovakia, China, and Australia. They indicate how managers make use of tools and techniques to solve problems associated with supply chains to reduce their cost and remain competitive. A great effort has been made to analyze this problem, and the methodologies are clearly described here to facilitate the reproducibility of each technique and tool. This was done in the hope that hoping that they may one day be applied in more companies.